A GLIMmer of insight into lung transplant nutrition: Enhanced detection of malnutrition in lung transplant patients using the GLIM criteria. Issue 5 (May 2021) - Emsley, Christie; King, Susannah; Nyulasi, Ibolya; Snell, Gregory
Summary: Background & aims: The Global Leadership Initiative on Malnutrition (GLIM) is a novel framework for diagnosing malnutrition and requires evaluation in wide-ranging clinical settings. This study aimed to assess the prevalence of malnutrition and its phenotypic characteristics among lung transplantation (LTx) candidates comparing GLIM to International Classification of Diseases, 10th Revision (ICD-10) criteria. Methods: A retrospective analysis was conducted of all adult patients assessed for LTx in a one-year period. Phenotypic criteria included body mass index (BMI), unintentional loss of weight (LOW) over a 12-month period and fat-free mass index (FFMI) using bioelectrical impedance analysis (BIA). Systemic inflammation associated with severe end-stage lung disease met GLIM's etiological criterion. Diagnosis of malnutrition, and its severity, were classified according to each of GLIM and ICD-10. Results: Of 130 patients, 112 (86%) had all data to classify malnutrition. Malnutrition prevalence according to GLIM was 59%, which was markedly greater than using ICD-10 criteria (26%). Half of the LTx patients were moderately malnourished using GLIM, compared to 19% using ICD-10. A similar proportion were severely malnourished using GLIM (9%) and ICD-10 (7%). Fat-free mass (FFM) depletion (47% of all patients) was a major contributor to GLIM-malnutrition. Over 60% of LTx patients with GLIM-malnutrition were not detected as malnourished using ICD-10 criteria. Conclusion: Malnutrition diagnosis using GLIM was higher than using ICD-10 in LTx patients, primarily attributable to the incorporation of quantitative evaluation of FFM depletion. This highlights the utility of the GLIM framework and the importance of including body composition in malnutrition assessment.